Hibridisasi Ikan Nila Pandu dan Kunti Generasi f4 Terhadap Efek Heterosis pada Ikan Nila Larasati (Oreochromis niloticus) Generasi F4 Pada Umur 5 Bulan - Vrahmana, Arief; Basuki, Fajar; Rejeki, Sri (Journal of Aquaculture Management and Technology, 2013)
The purpose of this research is measure the difference of heterocyst effect between tilapia larasati F4 fish ♂, tilapia pandu F4 fish ♂, and tilapia kunti F4 fish ♂, and between tilapia larasati F4 fish ♀, tilapia pandu F4 fish ♀, and tilapia kunti F4 fish ♀ in their age of five months. This research took place in Janti Freshwater Fish Hatchery and Aquaculture Unit, Klaten, from October-November 2012. The fish samples were ♂ and ♀ of F4 generation Larasati tilapia, F4 generation Pandu tilapia, and F4 generation Kunti tilapia at the age of 5 month. The rearring treatment lasted in 30 days. This research applied 3 treatment and 3 replications for each sex. The variables measured were weight, total length, thickness, survival rate (SR), relative growth rate (RGR), feed conversion ratio (FCR), and heterosis value of each variable. The Heterosis value of F4 generation Larasati tilapia at the age of 5 months are as follows SR ♂ and ♀ 1.66% 2.20%; weight ♂ ♀ 14.11% and 23.99%; total length ♂ ♀ 11.05% and 21.24%; thick ♂ ♀ 10.43% and 20.94%; and FCR ♂ ♀ 0.59% and 0.38%. Water quality during the research is still in a decent range for tilapia life is temperature 25.8 – 29oC; pH 6.7 to 7.7, and DO from 4.30 to 5.00 mg/ l.